Low concentrations of bilirubin inhibit activation of hepatic stellate cells in vitro - Tang, Yinhe (Mol Med Rep, 2017)
Hepatic stellate cell (HSC) activation serves a key role in liver fibrosis, and is associated with chronic liver diseases. Bilirubin, a product of heme degradation, has been demonstrated to have antioxidant properties. The present study investigated the effects of physiological concentrations of bilirubin on rat HSC activation. Rat HSCs were isolated and cultured for several generations to induce activation. The activated HSCs were subsequently treated with 0, 1, 10 or 20 mg/l bilirubin and assayed for parameters of cell activation. As the bilirubin concentration increased, HSCs demonstrated reduced production of reactive oxygen species, reduced protein expression levels of α-smooth muscle actin, a decreased mRNA expression ratio of tissue inhibitor of matrix metalloproteinase-1/matrix metalloproteinase-2, decreased proliferation and increased apoptosis. In conclusion, elevated bilirubin levels, within its physiological concentration range, appeared to inhibit HSC activation. These findings suggested a potential role for bilirubin in the treatment of fibrosis that requires further investigation.